Case Study of Educational Psychology Using Behavioristic Theory - Upi Lutpiah; Ajat Rukajat; Yayat Herdiana (Altruistik : Jurnal Konseling dan Psikologi Pendidikan, 2021)
The goal of this research is to look at a case study of educational psychology that uses behavioristic theory at Edelwis PAUD in Bekasi Regency, West Java. Teachers and students at PAUD Edelwis were the subjects of this study. Interviews, documentation, and observation were utilized as research tools in a qualitative approach that was documented descriptively. The research was conducted based on the study's findings. Indicates that practically all of the teachers at PAUD Edelwis have applied behavioristic theory since the school's inception. As in the case of the instructor who explains in front of the class and writes the alphabet and numbers on the blackboard, when the learning process begins, the pupils write in their respective books under the teacher's instruction and model. The students hand in their notebooks to the teacher. The application of this behavioristic theory to PAUD (Early Childhood Education) is very appropriate and effective in learning, according to the author. When the learning process began, the students that attended the lesson were quite eager and active in the classroom. Keywords: Behavioristic Theory; Educational Psychology Case Study on the Application of Behavioristic Theory